Penerapan Media "Papan Hitung Polinomial (PHP)" Sebagai Upaya Penguatan Pemahaman Konsep Polinomial Siswa SMA - Putri Handini, Wheni; Fikriyah, Alif Zakiyatul; Tristanti, Lia Budi (Jurnal Pengabdian Masyarakat, 2025)
This community service activity is based on issues encountered by the partner institution, MA Sains Tebuireng Kesamben, MA Sains Tebuireng Kesamben. The key issues identified include: (1) low student engagement during mathematics lessons, (2) a predominant reliance on PowerPoint presentations and lecture-based teaching methods by mathematics teachers, and (3) the absence of the use of the “Papan Hitung Polinomial (PHP)” as an instructional medium at the school. To address these issues, the PHP was introduced as an innovative teaching tool aimed at enhancing students’ conceptual understanding of polynomial operations. The purpose ot this service is to enhancing students’ conceptual understanding in solving polynomial operations consisting of polynomial addition, subtraction, multiplication, and division through PHP media.. The implementation process consisted of four main phases: preparation, execution, evaluation, and reporting. PHP media is effective for learning if more than 75% of students complete it. The results of the implementation PHP show that 95% of students were able to achieve the minimum value. Therefore, PHP learning media is an effective instructional medium, facilitating the teaching and learning process while significantly improving students’ understanding of polynomial concepts in MA Sains Tebuireng Putri and can be applied to other classes. Furthermore, the intervention positively impacted both teachers and students: teachers developed greater proficiency in utilizing the PHP, and students exhibited increased motivation and engagement. Overall, this community service activity contributed to a more practical and student-centered approach to mathematics instruction.